Legal Regulation of Electronic Journalism in Algeria: Analytical Study of the Media Law 12/05 - بومشطة، نوال (جامعة عمار ثليجي الأغواط - مخبر التمكين الاجتماعي والتنمية المستدامة في البيئة الصحراوية, 2023)
تهدف الدراسة إلى التعرف على التنظيم القانوني للصحافة الإلكترونية في الجزائر من خلال قانون الإعلام 05/12، والكشف عن حدود وضوابط الممارسة المهنية للصحافة الإلكترونية والمسؤوليات المترتبة عليها بالنسبة للصحفي والمؤسسة النشر، وذلك من خلال استخدام المنهج الوصفي الاستقرائي، لتحليل المواد القانونية التي تنص على تنظيم مهنة الصحافة الإلكترونية. توصلت الدراسة إلى نتائج أبرزها أن قانون الإعلام الجزائري 05/12 قدم تعريفا شاملا للصحافة الإلكترونية، ولم يراع خصائص ومميزات هذا النوع من الصحافة، كما أنه لم يحدد مهام ومسؤوليات الصحفي الإلكتروني، كما اعتبر الصحافة الإلكترونية هي تلك الاتصال المكتوب على شبكة الإنترنت، واستثنى التي لها نسخة ورقية ومنه حصرها في نوع واحد. The study aims to get acquainted the legal regulation of electronic journalism in Algeria through the media law 12/05, and to reveal the limits and controls of the professional practice of electronic journalism and the responsibilities that it entails for the journalist and the publishing institution, through the use of descriptive inductive approach, to analyze the legal materials that provide for the regulation of the electronic journalism profession. The study concluded, most notably, that the Algerian media law 12/05 provided a comprehensive definition of electronic journalism, and did not take into account the characteristics and features of this type of journalism, and it did not define the tasks and responsibilities of an electronic journalist, and considered electronic journalism to be those written communication on the internet, and excluded those that have a paper version and from it limited to one type.
Keywords: التنظيم القانوني -- الصحافة الإلكترونية -- القوانين الإعلامية -- الجزائر